Strategi Pemasaran di Ladang Anggrek Saraswanti Grup Kecamatan Pungging Kabupaten Mojokerto - Adipurwanto, M. Candra; Salbiyah, Siti Salbiyah; Danurwindo, Muhammad Alhakim (Improvement: Jurnal Manajemen dan Bisnis, 2023)
The purpose of this observation is to find out the marketing strategy at the Saraswanti Group Orchid Farm, Pungging District, Mojokerto by using the 7P marketing mix, then find out the obstacles in marketing orchid flowers and find out the promotional mix used at the Saraswanti Group Orchid Farm. The method used in this research uses a qualitative approach, with data collection techniques including observation, interviews, documentation and triangulation. The informants in this study included 1 person as the main source and 2 people as supporters. The results of this research show the Marketing Strategy used in marketing orchid flowers at the Saraswanti Group Orchid Farm (1) Through the Orchid Gallery (2) Online on social media Tik-tok, Facebook, Instagram, WA (3) The nearest flower shop in Mojokerto, Surabaya and Sidoarjo. Obstacles in marketing and producing orchids at the Saraswanti Group Orchid Farm are tight price competition and the long cultivation time for orchids, which takes 2 years. The promotion mix used at the Saraswanti Group Orchid Farm includes 5 main aspects, namely (1) Using advertising properly, distributing brochures and social media (2) Sales promotions providing special discounts for large buyers (3) Publicity by participating in events in cities and exhibitions (4) Selling charms through the orchid gallery (5) Direct marketing through the Orchid Farm website. Keywords: Orchid Farm Marketing Strategy, Marketing Mix, Qualitative Tujuan dari pengamatan ini adalah untuk mengetahui Strategi Pemasaran di Ladang Anggrek Saraswanti Grup Kecamatan Pungging Kabupaten Mojokerto dengan menggunakan bauran pemasaran 7P, kemudian mengetahui hambatan dalam memasarkan bunga anggrek dan mengetahui bauran promosi yang di gunakan di Ladang Anggrek Saraswanti Grup. Metode yang di gunakan dalam penelitian ini menggunakan pendekatan kualitatif, dengan teknik pengumpulan data meliputi, observasi, wawancara, dokumentasi dan triangulasi. Informan dalam penelitian ini meliputi 1 orang sebagai sumber utama dan 2 orang sebagai pendukung. Hasil penelitian ini menunjukkan Strategi Pemasaran yang di gunakan dalam memasarkan bunga anggrek di Ladang Anggrek Saraswanti Grup (1) Melalui Galery Anggrek (2) Secara Onlain media sosial Tik-tok, Facebook, Instagram, WA (3) Toko bunga terdekat yang ada di Kota Mojokerto, Surabaya dan Sidoarjo. Hambatan dalam memasarkan dan memproduksi bunga anggrek di Ladang Anggrek Saraswanti Grup yakni persaingan harga yang ketat dan lamanya waktu budidaya bunga anggrek yang memakan waktu 2 tahun. Promosi mix yang digunakan di Ladang Anggrek Saraswanti Grup mencakup 5 aspek utama yakni (1) Periklanan (2) Promosi penjualan (3) Publisitas (4) Penjualan pesonal (5) Pemasaran langsung Kata Kunci: Anggrek, Strategi Pemasaran, Bauran Pemasaran, Kualitatif